Uji Larvasida Dan Repelansia Beberapa Ekstrak Tumbuhan Pada Nyamuk Culex SP - Mahdy A, Al (UI Scholars Hub, 2006)
There is a plethora of evidence to suggest that host seeking in mosquitoes is medicated by infochemicals or semichemicals emanating from the host and visual clues that the mosquitoes recognize. The objectives of this research was to evaluate larvacidal and repellant effect of several herbal extracts that repell the mosquitoes. The result shown that ethanolic extract of Piper aduncum effective as larvacide for the first instar of Culex sp, while extract of Canangium odoratum repelled almost all of the female mosquitoes treated.